2006
DOI: 10.1007/bf03349194
|View full text |Cite
|
Sign up to set email alerts
|

Increased lipid peroxidation in adult GH-deficient patients: Effects of short-term GH administration

Abstract: These data support the view that adult GHD syndrome is characterized by an unbalance between pro- and anti-oxidant factors with marked preponderance of the former. This abnormality, likely contributing to the increased atherogenic risk of GHD patients, is corrected by short-term GH administration at a dose able to increase, although not to fully normalize, IGF-I levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…1 mg/kg GH was able to exert beneficial effects enhancing antioxidant defences, reducing oxidative stress and improving energy generation in the myocardium of rats with heart failure (Seiva et al 2008). Also, GH replacement was able to partially reverse the abnormally increased LPO (KarbownikLewinska et al 2008) and to significantly prolong lag-time (index of anti-oxidant activity) in GHdeficient adults (Scacchi et al 2006). Previous studies from our group have shown that GH could also improve some parameters related to the oxidative damage (LPO, NO levels) associated with aging in hepatocytes isolated from old female and male rats (Castillo et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…1 mg/kg GH was able to exert beneficial effects enhancing antioxidant defences, reducing oxidative stress and improving energy generation in the myocardium of rats with heart failure (Seiva et al 2008). Also, GH replacement was able to partially reverse the abnormally increased LPO (KarbownikLewinska et al 2008) and to significantly prolong lag-time (index of anti-oxidant activity) in GHdeficient adults (Scacchi et al 2006). Previous studies from our group have shown that GH could also improve some parameters related to the oxidative damage (LPO, NO levels) associated with aging in hepatocytes isolated from old female and male rats (Castillo et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The increased blood LPO level in GH-deficient adults has been reported 10 and confirmed in the present study. Other authors also found increased oxidative damage to lipids [7][8][9] or to DNA in GHdeficient patients. 11 Such findings justify the conclusion that redox imbalance exists in GH-deficient patients.…”
Section: Discussionmentioning
confidence: 87%
“…In the first one, 4 months of GH replacement decreased plasma lipid peroxide concentration, however, the parameter, measured in that study, represents oxidative damage to LDL-cholesterol exclusively. 9 In the second, 6 months of GH replacement decreased oxidized guanosine (the product of oxidative DNA damage) urine excretion described in a report of a single investigated patient. 11 Both of these parameters differ from those evaluated in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…In this regard, after 24 weeks of GH replacement therapy in the GREAT study, the hormone significantly lowered plasma diacron-reactive oxygen metabolites and improved endothelial function, as measured by reactive hyperemia index [145]. This indicates that GH can exert a protective role in redox balance in GHD, in which predominates a pro-oxidant environment, corrected by short-term GH administration [146]. Klotho, a GH-releasing factor that currently is gaining in interest, also lowers the oxidative stress, decreasing apoptosis and senescence of the vascular system in an atherogenic risk rat model [147].…”
Section: Cellular Senescence and Wound Healing: Benefit Of Gh Therapymentioning
confidence: 92%